Collective bargaining in the platform economy: A mapping exercise of existing initiatives - Mariagrazia Lamannis (European Trade Union Institute (ETUI), 2023)
This paper presents the results of a mapping of social dialogue and collective bargaining experiences in the European platform economy. Building on a descriptive analysis of the initiatives, the report provides insights into collective bargaining strategies and factors that have led platforms to negotiate. It focuses on empirical and legal 'obstacles' encountered - both before and after negotiations - as well as on emerging good practices. With traditional unions playing the lead role, most initiatives are collective agreements concluded at company level. It also emerges that smaller platforms are more willing to engage in social dialogue, while larger players still have an attitude of avoidance as regards collective bargaining and labour law protections. Although collective agreements have marked an improvement in working conditions, many platform workers still do not have sufficient protection, and issues related to the peculiarities of the platform economy need to be better addressed. Coordinated and collaborative action by various actors (informal and traditional trade unions, institutions, consumers) is then suggested as a way to improve working conditions and simultaneously support companies complying with the law and collective agreements - hence effectively challenging the narrative of the economic unsustainability of labour protections in the platform economy.
Keywords: 330; Tarifverhandlungen